2006
DOI: 10.1074/mcp.m500426-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Universal Metrics for Quality Assessment of Protein Identifications by Mass Spectrometry

Abstract: Increasing numbers of large proteomic datasets are becoming available. As attempts are made to interpret these datasets and integrate them with other forms of genomic data, researchers are becoming more aware of the importance of data quality with respect to protein identification. We present three simple and universal metrics that describe different aspects of the quality of protein identifications by peptide mass fingerprinting. Hit ratio gives an indication of the signal-to-noise ratio in a mass spectrum, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 14 publications
0
43
0
Order By: Relevance
“…The researchers represented the results with receiver operating characteristic (ROC) plot, which displayed the ratio of true positive classifications to the fraction of false positives (1-specificity) as a function of discriminatory performance. 33,34 The larger area under the curve indicates the better performance of discrimination. Herein, the confirmed results of each strategy were defined as the correct matches, whereas the highest ranked proteins in CRRSDB were taken as the incorrect matches.…”
Section: Comparison Of Strategies For Test Datasetmentioning
confidence: 97%
See 1 more Smart Citation
“…The researchers represented the results with receiver operating characteristic (ROC) plot, which displayed the ratio of true positive classifications to the fraction of false positives (1-specificity) as a function of discriminatory performance. 33,34 The larger area under the curve indicates the better performance of discrimination. Herein, the confirmed results of each strategy were defined as the correct matches, whereas the highest ranked proteins in CRRSDB were taken as the incorrect matches.…”
Section: Comparison Of Strategies For Test Datasetmentioning
confidence: 97%
“…33 It has been reported that ELDP can discriminate between correct and random matches more accurately than the search score of MASCOT. The researchers represented the results with receiver operating characteristic (ROC) plot, which displayed the ratio of true positive classifications to the fraction of false positives (1-specificity) as a function of discriminatory performance.…”
Section: Comparison Of Strategies For Test Datasetmentioning
confidence: 99%
“…Based on the ranking, data acceptability decisions can be made by choosing suitable thresholds on the ordered set. Such a score model for protein hits has indeed been proposed by a group of collaborators at the Aberdeen Proteomics Facility [6]. The model has two interesting properties, namely (i) it shows excellent true positive-to-false positive ratio performance on extensive test sets; and (ii) it is computed using parameters that are common to most available PMF matching algorithms, regardless of their proprietary nature.…”
Section: Introductionmentioning
confidence: 98%
“…Recent research [11] has shown a strong correlation between a simple score model for matches based on this and other readily available indicators, and the likelihood of false positives. By using this predictive score model to rank the output of the matching service, in combination with a user-defined threshold, experimenters have an effective way to make their quality acceptance criteria formal and automatically computable.…”
Section: Examplementioning
confidence: 99%